Analysis of different standards for life support technology in manned submersible - Jiang, Lei; Ye, Cong; Li, Hongxia; Wang, Yao; Jiang, Nian (Frontiers in Physiology, 2024)
Life support technology is one of the most critical technologies in manned submersibles, acting for the pilots of the submersible and thus directly affecting its underwater safety. Due to its importance, many countries and international organizations have proposed standards and specifications for life support technology. This paper presents an overview of the life support technology of manned submersibles, comparing the standards proposed for it. Furthermore, it analyzes the specific data of oxygen supply and carbon dioxide absorption, both of which are critical aspects of life support technology in each standard, and identifies the data that is widely acknowledged and recognized as the basis for establishing ISO standard 22252:2020). Finally, ISO standard data such as oxygen and carbon dioxide concentration are further confirmed by the environmental parameters of manned submersibles such as the Fendouzhe.